2017
DOI: 10.1186/s12917-017-0975-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and virulence clustering analysis of extraintestinal pathogenic Escherichia coli isolated from swine in China

Abstract: BackgroundSwine extraintestinal pathogenic Escherichia coli (ExPEC) is an important pathogen that leads to economic and welfare costs in the swine industry worldwide, and is occurring with increasing frequency in China. By far, various virulence factors have been recognized in ExPEC. Here, we investigated the virulence genotypes and clonal structure of collected strains to improve the knowledge of phylogenetic traits of porcine ExPECs in China.ResultsWe isolated 64 Chinese porcine ExPEC strains from 2013 to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The analysis of the distribution of VGs within phylogenetic groups among E. coli from sows revealed no significant differences, the one exception being isolates of phylogroup A, which carried VGs significantly less frequently. Our results demonstrating the virulence potential of group B2 in isolates from piglets are consistent with those presented in the first, above-mentioned report concerning ExPEC [26]. On the other hand, it was also reported that VGs were distributed among four main phylogroups without significant differences in commensal porcine isolates [12], which is consistent with our analysis concerning E. coli from sows.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The analysis of the distribution of VGs within phylogenetic groups among E. coli from sows revealed no significant differences, the one exception being isolates of phylogroup A, which carried VGs significantly less frequently. Our results demonstrating the virulence potential of group B2 in isolates from piglets are consistent with those presented in the first, above-mentioned report concerning ExPEC [26]. On the other hand, it was also reported that VGs were distributed among four main phylogroups without significant differences in commensal porcine isolates [12], which is consistent with our analysis concerning E. coli from sows.…”
Section: Discussionsupporting
confidence: 93%
“…According to the definition (Johnson et al [10]) 17.3% of E. coli isolates from piglets and 7.9% from sows were classified as ExPEC, despite the fact that they were derived from healthy animals. The other isolates in our collection also harbored VGs associated with the ability to cause extraintestinal disease, not only in swine but also in humans [4,26]. The results showed significant differences between isolates from piglets and sows.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations